2007
DOI: 10.1002/lsm.20519
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocity of exposure time and irradiance on energy density during photoradiation on wound healing in a murine pressure ulcer model

Abstract: Varying irradiance and exposure time to achieve a specified energy density affects phototherapy outcomes in this model. Variation of exposure time and irradiance may account for conflicting results in the literature. Further studies of these effects are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
85
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 22 publications
4
85
1
1
Order By: Relevance
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 64%
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 64%
“…Our laboratory demonstrated that cell proliferation and metabolism in vitro can be influenced by varying the dose frequency or treatment interval of the PBMT (17). We have also demonstrated this same phenomenon as regards wound healing in a murine pressure ulcer model (18). These investigations underscore the concept that a unique dose frequency combination exists for tissues and cell lines and that this specific treatment paradigm must be determined to optimize outcomes and maximally stimulate cellular metabolism and proliferation.…”
mentioning
confidence: 54%
“…Light at this wavelength is known to be absorbed by cytochrome C oxidase and other molecules, stimulating ATP synthesis and affecting ROS production, among numerous other activities at the cellular, tissue and whole organism level (16). The caveat however is that the light dose and dose rate are important and that all cell and tissues are not equally responsive to photoradiation (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
See 2 more Smart Citations